"We went and did an Anzac job": Memory, Myth, and the Anzac Digger in Vietnam. (5th October 2018) - Martin Hobbs, Mia
Abstract : Australian martial identity is defined by the Anzac legend, and Australian veterans of all wars have struggled to remember their service through the prism of Anzac. For Australia's Vietnam veterans, this struggle is particularly complex: powerful memories of conflict and division contest the values of Anzac. This oral history shows how Vietnam veterans' personal memories of war are modified into tropes to create a collective identity of victimhood. Several historians have explored individual tropes that appear in veterans' memories. This article, based on qualitative interviews with Vietnam veterans, builds on their work and identifies six memory tropes: the volunteer Nasho, the noble and skilful digger, no welcome home, baby killer, banned from the RSL, and belated recognition. Together, these tropes constitute a "cultural script" that retells the story of Anzac in Vietnam. This cultural script is a way for veterans to express their feelings of exclusion from Anzac status in Australia, and a way for them to reclaim this status. However, deconstructing the script shows how unattainable the ideal of Anzac is, requiring an ongoing creation of victimhood to legitimise martyrdom and further perpetuating the hierarchies of Anzac identity.